Electronic, structural and optical properties of Gd-doped ZnO powder synthesized by solid-state reaction method - Gora, Mahendra Kumar; Kumar, Arvind; Choudhary, Banwari Lal; Dolia, Satya Narain; Kumar, Sanjay; Singhal, Rishi Kumar (Bangladesh Journal of Scientific and Industrial Research, 2023)
We explored the impact of Gd doping on the structural, electronic and optical characteristics of the ZnO powder. The Gd-doped ZnO (0, 2% and 5%) powder samples have been synthesized using the conventional solid-state reaction process with varied Gd concentrations. The XRD pattern confirmed that all the studied samples are in the hexagonal wurtzite crystalline structure. The morphology has been explored using SEM images, which exhibited an agglomerated rod-like particle structure. The XPS results indicate the presence of oxygen vacancies (Vo) in the Gd-doped ZnO samples and the Vo’s are found to increase with increasing Gd amount. According to PL findings, the intensity ratio of the green and ultra-violet emission peaks is found to increase from 0.090 to 0.418 with increasing Gd-doping concentrations, confirming that Vo’s are increasing with Gd-doping. The UV-visible spectroscopy results reveal that the energy band gap (Eg) decreased from 3.31 eV to 3.23 eV with increasing Gd-doping concentration. Bangladesh J. Sci. Ind. Res. 58(1), 53-64, 2023